PELATIHAN PENYUSUNAN LAPORAN KEUANGAN MELALUI PEMANFAATAN APLIKASI EXCEL PADA MASJID DESA LUMBANG - Eliza Noviriani; U Ari Alrizwan; Lailatul Mukaramah (Politeknik Negeri Sriwijaya, 2021)
This PKM activity aims to provide financial administration assistance and training specifically in the preparation of financial reports according to PSAK No. 45 by using the excel application. The training participants were each mosque takmir in 3 (three) Desa Lumbang mosques, namely the Chair, Secretary and Treasurer of Darut Taqwa Mosque in Penyengat Hamlet, Hamdalah Mosque in Nengen Hamlet and Al-Kautsar Mosque in Keramat Hamlet. This training approach uses lecture, discussion and practice methods. After the training using the lecture, practice and discussion methods, there were significant changes in the participants. This is indicated by the ability of participants to begin to recognize and identify transactions as well as journalize. In addition, based on the testimonies of participants' representatives, this training provided enlightenment to participants from being completely blind to accounting to understanding the process of preparing financial reports. Good changes were also seen from the participants' interest in